Effectiveness of a rehabilitation protocol after anterior cruciate ligament reconstruction in returning to match rhythm: a case study of a professional soccer player - Kacprzak, Bartłomiej; Siuba, Natalia; Miler, Adrian; Kitchke, Ewa; Hagner-Derengowska, Magdalena; Zukow, Walery (Journal of Education, Health and Sport, 2024)
This case study presents the rehabilitation process of professional soccer player M.L. after surgical reconstruction of the anterior cruciate ligament (ACL) using the BTB method. Rehabilitation, lasting 3.5 months, enabled a quick return to the game. The course of treatment was based on an intensive rehabilitation protocol without the use of an orthosis, with early weight-bearing of the limb and focusing on rebuilding strength, stability and proprioception. Evaluation of the effectiveness of rehabilitation was carried out using functional tests and questionnaires KOOS, Kujala, SF-36.